2015
DOI: 10.1161/jaha.115.002527
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor–Related Apoptosis‐Inducing Ligand (TRAIL) Promotes Angiogenesis and Ischemia‐Induced Neovascularization Via NADPH Oxidase 4 (NOX4) and Nitric Oxide–Dependent Mechanisms

Abstract: BackgroundTumor necrosis factor–related apoptosis‐inducing ligand (TRAIL) has the ability to inhibit angiogenesis by inducing endothelial cell death, as well as being able to promote pro‐angiogenic activity in vitro. These seemingly opposite effects make its role in ischemic disease unclear. Using Trail −/− and wildtype mice, we sought to determine the role of TRAIL in angiogenesis and neovascularization following hindlimb ischemia.Methods and ResultsReduced vascularization assessed by real‐time 3‐dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 42 publications
2
69
0
Order By: Relevance
“…VEGF-A and FGF-2 are established pro-angiogenic growth factors, known to promote EC proliferation [6]. TRAIL can also induce EC proliferation in vitro and in vivo [4]. To date, a comprehensive analysis of TRAIL, VEGF-A and FGF-2 or the effect of combination treatment on EC proliferation has not been examined.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…VEGF-A and FGF-2 are established pro-angiogenic growth factors, known to promote EC proliferation [6]. TRAIL can also induce EC proliferation in vitro and in vivo [4]. To date, a comprehensive analysis of TRAIL, VEGF-A and FGF-2 or the effect of combination treatment on EC proliferation has not been examined.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a comprehensive analysis of TRAIL, VEGF-A and FGF-2 or the effect of combination treatment on EC proliferation has not been examined. We treated HMEC-1 cells with 10 ng/mL TRAIL, 50 ng/mL VEGF-A and 50 ng/mL FGF-2, doses known to stimulate cell proliferation [4]. TRAIL at 10 ng/mL promoted HMEC-1 proliferation just as effectively as VEGF-A at 50 ng/mL (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, studies using systemic NOX4 KO mice cannot distinguish the effect of NOX4 in CMs from its effect in non-CMs. NOX4 enhances angiogenesis under ischemic conditions and is therefore protective against ischemic injury in lower limbs (35). Furthermore, Chen et al demonstrated that endothelial NOX4 mediates angiogenesis (36).…”
Section: Discussionmentioning
confidence: 99%